Effect of BCZT on electrical properties and bioactivity of 45S5 bioglass - Nuttapon Pisitpipathsin (2018)
In this work, ferroelectric Ba0.92Ca0.08Zr0.05Ti0.95O3/45S5 bioglass composite or (BCZT/45S5 composite) has been produced for orthopedic applications. The BCZT concentrations ranged from 0-15 wt.%. The BCZT/45S5 composite was prepared by conventional melting method at 1300°C for 1 h following by heat treatment schedule at the crystallization temperatures of glass. The effects of BCZT addition on the dielectric and piezoelectric properties and the biocompatibility of BCZT/45S5 composites were investigated. It was found that, the addition of BCZT improved the hardness and dielectric properties of materials, which may be caused by the presence of the BCZT. Moreover, the bioactivity of the 45S5 bioglass was improved with addition of BCZT phase as evident by the formation of bone like apatite layers on the surface of all BCZT/45S5 composites after soaking in simulated body fluid (SBF). Copyright © Taylor & Francis Group, LLC.